2020
DOI: 10.1111/1440-1681.13372
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontitis and hyperlipidaemia: A systematic review and meta‐analysis

Abstract: is a chronic inflammatory disease in the oral cavity that usually affects the adult population. 1,2 PD is characterized by gingival bleeding, periodontal pocket formation and clinical attachment loss (CAL), 3 and potentially associated with some factors, such as diabetes mellitus, smoking and obesity. Hyperlipidaemia is a heterogeneous group of disorders characterized by elevated TG, TC, LDL levels and decreased HDL level. Hyperlipidaemia is associated with chronic inflammation, 4 which in turn causes a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
(139 reference statements)
1
12
0
1
Order By: Relevance
“…Several studies have reported associations between periodontitis and elevated levels of both systolic and diastolic blood pressure, increased likelihood of hypertension and higher serum triglyceride and total cholesterol levels, which further support our findings (Muñoz Aguilera et al, 2020; Xu & Duan, 2020). Furthermore, previous research has also demonstrated that diabetes, especially uncontrolled diabetes, is a risk factor for periodontitis and tooth loss (Genco & Borgnakke, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported associations between periodontitis and elevated levels of both systolic and diastolic blood pressure, increased likelihood of hypertension and higher serum triglyceride and total cholesterol levels, which further support our findings (Muñoz Aguilera et al, 2020; Xu & Duan, 2020). Furthermore, previous research has also demonstrated that diabetes, especially uncontrolled diabetes, is a risk factor for periodontitis and tooth loss (Genco & Borgnakke, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Our results are similar to the previously reported association between periodontitis and dyslipidemia. A meta-analysis also showed that periodontal disease was associated with hyperlipidemia [ 26 ]. Gomes-Filho et al showed that patients with periodontitis were 1.47 times more likely to have a TG/HDL-C ratio ≥ 2.3 than patients without periodontitis, indicating a positive association between periodontitis and dyslipidemia [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have focused on the potential pro-atherogenic alterations in plasma lipids and lipoproteins, since dyslipidemia is a common feature of patients with periodontitis; a systematic review and meta-analysis of published studies revealed that periodontitis is associated with higher plasma levels of total- and LDL-cholesterol and triglycerides, with a concomitant decrease of HDL-cholesterol concentrations [ 63 ]. Yet, beyond the increased concentrations of LDL-cholesterol, untreated periodontitis is also associated with an altered LDL subclass profile, with a predominance of atherogenic small dense LDL [ 64 ]; this means, therefore, that patients with periodontitis have alterations in both the quantity and the quality of LDL, which represents a well-known mechanism for the development of pro-atherogenic alterations and the enhancement of cardiovascular risk [ 65 ].…”
Section: Effects Of Periodontal Treatment On Systemic Health In Both ...mentioning
confidence: 99%